Light scattering in the plastic scintillator - Khalapova, N.; Shpilevoy, Ya.; Senchyshyn, V.; Gavrik, A.; Lebedev, V. (Functional Materials, 2007)
Optical losses in a standard composition plastic scintillator (PS) (98.5 %PST + 1.5 p-TP + 0.02 % POPOP) have been analyzed numerically. The PS scattering properties have been studied in experiment for PS samples manufactured under two different large-size block polymerization conditions. The total scattering data and bulk attenuation length of light in PS are presented. Contributions from individual scattering components (Rayleigh and Mie scattering) have been estimated basing on a simplified model. The observed Rayleigh scattering component reduction from 1850 to 380 dB/km after additional annealing can be explained by a decrease in local polymer matrix heterogeneity.